PENGARUH PENGETAHUAN KEWIRAUSAHAAN, LINGKUNGAN SOSIAL DAN KEPRIBADIAN TERHADAP MOTIVASI BERWIRAUSAHA MAHASISWA TEKNIK INFORMATIKA UNTAG SURABAYA - Wanti, Desiani Kurnia; Pujianto, Agung; Nasution, Ute Ch (Research Journal of Social Science and Economics, 2025)
Every year there is an increase in population which results in unemployment due to the lack of employment opportunities. The purpose of this study was to determine the effect of Entrepreneurial Knowledge, Social Environment and Personality on Entrepreneurial Motivation. This study used a quantitative research type method with data collection techniques using a questionnaire. Respondents to this study were 83 Informatics Engineering students at UNTAG Surabaya class of 2019-2020 who had taken entrepreneurship courses. This study used instrument tests, classical assumption tests, multiple linear regression tests and hypothesis testing which included the t test and F test. The results of the data analysis showed that the t test produced tcount for Entrepreneurship Knowledge of 2.393> 1.664, tcount for the Social Environment of 3.438> 1.664 and the results of the t test for Personality are 3.097> 1.664. So it can be concluded that tcount>ttable, which means that there is a significant influence between the variables of Entrepreneurship Knowledge, Social Environment and Personality on Entrepreneurial Motivation. The F test produces an fcount of 29.642 with a significant level of 0.000. The results of the F test show that the value of fcount is 29.642> f table is 3.09, then Ho is rejected and Ha is accepted. The recommendations in this study are expected to have an impact on the application of the Entrepreneurship Knowledge, Social Environment and Personality variables in encouraging Informatics Engineering Students at UNTAG Surabaya to have Entrepreneurial Motivation.